Understanding the UI Population in Milwaukee County - (:unkn) unknown (My University, 2010)
The number of Milwaukee County residents receiving unemployment insurance because of layoffs has tripled over the last three years, as workers remain on UI while seeking out retraining and searching for new employment. As of March 2010 over 50,000 workers were receiving UI payments instead of pay checks. Serving workers who have been laid off from their jobs and are trying to find new employment and to upgrade their skills is one of the most challenging tasks facing the Milwaukee Area Workforce Investment Board (MAWIB). This analysis uses unemployment insurance records and state wage file matches to profile workers’ employment history and current job status to help MAWIB target and measure services for unemployed and underemployed workers, identify need levels of newly laid-off workers, and prioritize services for subpopulations seeking assistance. The analysis is designed to help improve delivery of services to unemployed workers by expanding outcome data for use in assessing the effectiveness of programs for WIA clients and identifying gaps in programs and services.
Keywords: unemployment insurance; displaced workers